2003
DOI: 10.1038/sj.onc.1206961
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative metabolism, gap junctions and the ionizing radiation-induced bystander effect

Abstract: Evidence accumulated over the past two decades has indicated that exposure of cell populations to ionizing radiation results in significant biological effects occurring in both the irradiated and nonirradiated cells in the population. This phenomenon, termed the 'bystander response', has been shown to occur both in vitro and in vivo and has been postulated to impact both the estimation of risks of exposure to low doses/low fluences of ionizing radiation and radiotherapy. Several mechanisms involving secreted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
233
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(238 citation statements)
references
References 91 publications
4
233
1
Order By: Relevance
“…In this phenomenon, IR-damaged cells pass a signal to unirradiated cells, triggering certain signaling pathways and producing genomic instability and cytotoxicity in the untreated cells (33)(34)(35)(36). It is also known that toxic metabolites of pro-drugs can also be passed between cells through gap junctions [for example, 5-fluorouracil that has been converted from 5-fluorocytosine by cytosine deaminase (37)].…”
Section: Discussionmentioning
confidence: 99%
“…In this phenomenon, IR-damaged cells pass a signal to unirradiated cells, triggering certain signaling pathways and producing genomic instability and cytotoxicity in the untreated cells (33)(34)(35)(36). It is also known that toxic metabolites of pro-drugs can also be passed between cells through gap junctions [for example, 5-fluorouracil that has been converted from 5-fluorocytosine by cytosine deaminase (37)].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation exposure, in addition to inducing an acute damage response, also has a strong component of heritable instability, detected using in vitro immortalized cell systems , and in hematopoietic stem cells (Kadhim et al, 1992). The specific mechanisms involved are unclear, but continuous generation of reactive oxygen species has been proposed to be one of the factors responsible (Azzam et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon (bystander effect) is usually explained by cell-cell signalling between irradiated cells and closely located non-irradiated cells. Specifically, the bystander effect has been attributed to communication between irradiated and unirradiated cells by direct contact between neighbouring cells; signalling via specific substances in the nutrient medium of irradiated cells that influenced unirradiated cells and immunity-mediated responses [43,60,61]. Microarray studies revealed that the profile of gene expression in irradiated cells was different from that in unirradiated cells which exhibited evidence of bystander effect, with only part of the genes whose expression has been modulated in the irradiated cells being altered in unirradiated cells receiving media from irradiated cells [62].…”
Section: Bystander Effectmentioning
confidence: 99%